Attenuated iron stress and oxidative stress may participate in anti-seizure and neuroprotective roles of xenon in pentylenetetrazole-induced epileptogenesis - Zhang, Mengdi; Cheng, Yao; Zhai, Yujie; Yuan, Yi; Hu, Haoran; Meng, Xianfeng; Fan, Xuemeng; Sun, Hongliu; Li, Shucui (Frontiers in Cellular Neuroscience, 2022)
We verified the anti-seizure and neuroprotective roles of xenon in epileptogenesis and evaluated the involvement of oxidative stress and iron accumulation in the protective roles of xenon. Epileptogenesis was induced by pentylenetetrazole (PTZ) treatment in Sprague-Dawley rats. During epileptogenesis, we found increased levels of iron and oxidative stress accompanied by elevated levels of divalent metal transporter protein 1 and iron regulatory protein 1, which are closely associated with iron accumulation. Meanwhile, the levels of autophagy and mitophagy increased, alongside significant neuronal damage and cognitive deficits. Xenon treatment reversed these effects: oxidative stress and iron stress were reduced, neuronal injury and seizure severity were attenuated, and learning and memory deficits were improved. Thus, our results confirmed the neuroprotective and anti-seizure effects of xenon treatment in PTZ-induced epileptogenesis. The reduction in oxidative and iron stress may be the main mechanisms underlying xenon treatment. Thus, this study provides a potential intervention strategy for epileptogenesis.